Acute gastroenteritis in infants under 6 months old. Issue 9 (September 1990) - Fox, R; Leen, C L; Dunbar, E M; Ellis, M E; Mandal, B K
Abstract : Sixty two babies under the age of 6 months who were admitted with gastroenteritis completed a study of gradual refeeding compared with abrupt refeeding after a period of rehydration. There was no difference in the incidence of recurrence of diarrhoea due to lactose intolerance, effect on weight, or duration of hospital stay. Twenty six babies (42%) had recurrence of diarrhoea after refeeding, all of whom settled with the introduction of a lactose free soya based formula. Well nourished babies under 6 months of age with mild to moderately severe gastroenteritis can be fed immediately with full strength milk feeds after rehydration. The introduction of a lactose free soya based preparation may provide an alternative to repeated attempts at regrading with cows' milk feeds in those patients with lactose intolerance.